ELAZIĞ İLİNDE TÜKETİME SUNULAN ET VE BAZI ET ÜRÜNLERİNDE LİSTERİA TÜRLERİNİN ARAŞTIRILMASI - GÜVEN, ABAMÜSLÜM (Fırat Üniveristesi, 1994)
Bu çalışmada, Elazığ ilinde çeşitli satış yerlerinden temin edilen 100 kıyma, 80 tavuk eti, 80 sucuk ve 70 parça et örneğinde Listeria türleri araştırıldı. Örneklere, 30 °C'de 48 saat ve 1 hafta süren iki zenginleştirme yöntemi uygulanarak, Listeria Selective Agar Base (LSA), Modifiye McBride Agar (MMBA) ve McBride Agar'a (MBA) yapılan ekimlerin sonuçları değerlendirildi. Aynı örnekler -8 ±1 °C'de 10 gün bekletildikten sonra yeniden incelendi. 48 saat zenginleştirme işlemi sonunda kıyma örneklerinin % 13.0'ünde L monocytogenes, % 26.0'sında L innocua ve % 4.0'ünde ise her iki tür birlikte saptandı. Böylece örneklerin % 35.0'inde Listeria türleri tesbit edildi. 10 gün sonraki incelemede ise, L. monocytogenes % 10.0, L. innocua % 19.0 oranında olmak üzere örneklerin % 25.0'inde Listeria türleri saptandı. 7 gün zenginleştirmeden sonra, incelenen örneklerin % 9.0'unda L. monocytogenes, % 24.0'ünde L innocua olmak üzere % 31.0'inde Listeria türleri saptandı. 10 gün sonra yapılan incelemede ise, bu değerler sırasıyla % 7.0, % 18.0 ve % 23.0 olarak bulundu. 48 saatlik zenginleştirme yapıldıktan sonra, incelenen tavuk etlerinin % 38.8'inde L monocytogenes, % 50.0'sinde L. innocua ve % 60.0'ında Listeria türleri tesbit edildi. 10 gün sonraki incelemede ise örneklerin % 15.0'inde L monocytogenes, % 33.8'inde L innocua olmak üzere toplam % 37.5'inde Listeria türleri saptandı. 7 günlük zenginleştirmeden sonra, tavuk etlerinin % 26.3'ünde L. monocytogenes, % 43.8'inde L. innocua bulundu. 10 gün sonra bu değerler sırasıyla % 10.0 ve % 21.3 olarak tesbit edildi.76 incelenen sucuk örneklerinin, 48 saat zenginleştirme işleminden sonra, L. monocytogenes % 7.5, L innocua ise % 11.3 oranında saptandı. Listeria kontaminasyonu % 16.3 olarak bulundu. 10 gün sonra yapılan incelemede, L monocytogenes % 5.0, L innocua % 10.0 oranında bulundu. 7 gün süren zenginleştirmeden sonra, örneklerin % 6.3'ünde L. monocytogenes, % 8.8'inde L. innocua saptandı. İkinci incelemede bu değerler sırasıyla, % 2.5 ve % 6.3 olarak tesbit edildi. İncelenen parça et örneklerinin, 48 saat zenginleştirilmesi yapıldıktan sonra, % 11.4'ünde L. monocytogenes, % 18.6'sında L. innocua saptandı. Örneklerin % 28.6'sının kontamine olduğu görüldü. 10 gün sonraki incelemede L. monocytogenes % 7.1, L innocua % 12.9 olarak bulundu. 7 günlük zenginleştirme sonucunda, parça etlerin % 8.6'sında L monocytogenes, % 11.4'ünde L. innocua bulundu. İkinci incelemede L. monocytogenes % 5.7, L. innocua ise % 10.0 oranında saptandı. Sonuç olarak, Listeria türlerinin çeşitli et örneklerinden izolasyonunda, LSA besiyerinin, MMBA ve MBA besiyerlerine göre çok daha uygun olduğu görüldü. MMBA ve MBA besiyerlerinde benzer sonuçlar alındı. 48 saatlik zenginleştirme işlemi sonunda örneklerde elde edilen Listeria oranı, 7 günlük zenginleştirmeden daha fazla bulundu. -8 + 1 °C'de 10 gün bekletilen örneklerde Listeria türlerinin büyük çoğunluğunun canlı kaldığı saptandı. İncelenen et ürünlerinde, özellikle kıyma ve tavuk etlerinde L monocytogenes insidensinin fazla olduğu ve halk sağlığı açısından tehlike arzedebileceği kanısına varıldı.

In this study, presence of Listeria species in various meat products obtained from different meat markets in Elazığ city was studied. For this purpose 100 minced meat, 80 poultry meat, 80 sausage and 70 chopped-meat samples were analysed. The samples were incubated at 30 °C twice for 48 hours and 7 days respectively. These incubations were performed for enrichment of potential Listeria species in the samples which were inoculated onto Listeria selective agar base (LSA), Modifiye McBride agar (MMBA) and McBride agar (MBA) media. In addition the rest of the same samples were enriched at 30 °C for 48 hours and 7 days after being kept at -8 ± 1 °C for 10 days. At the end of initial 48 hours enrichment Listeria species were present in 35.0 % minced meat samples and the percentage of minced meat samples with Listeria monocytogenes, with Listeria innocua and with both Listeria species were 13.0, 26.0 and 4.0 % respectively. After 7 days enrichment L. monocytogenes and L. innocua were observed in 9.0 and 24.0 % of the samples respectively. In this examination overall positivity for Listeria species was 31.0 % in minced meat samples. After 48 hours and 7 days enrichments of the same samples that were kept previously at -8 ± 1 °C for 10 days L. monocytogenes were present in 10.0 and 7.0 % whilst L. innocua occurred in 19.0 and 18.0 % of the samples respectively. In this examination overall positivity for Listeria species in minced meat samples were 25.0 and 23.0 % considering 48 hours and 7 days enrichments respectively.78 In poultry meat after the a 48 hours enrichment L monocytogenes, L innocua and Listeria species were present 38.8, 50.0, 60.0 % of the samples respectively. After the 7 days enrichment 26.3 % of poultry meat had L. monocytogenes whilst L. innocua was present in 43.8 % of the same samples and overall positivity for Listeria species was 52.5 % in poultry meat samples. After 48 hours and 7 days enrichment of the same samples that were previously kept at -8 ± 1 °C for 10 days L. monocytogenes were present in 15.0 and 10.0 % whilst L. innocua occurred in 33.8 and 21.3 % of the samples respectively. In this examination overall positivity for Listeria species were 37.5 and 23.8 % in poultry meat samples considering 48 hours and 7 days enrichments respectively. In the sausage samples after 48 hours enrichment L. monocytogenes and L. innocua were determined in 7.5, 11.3 % of the samples whilst after 7 days enrichment period L. monocytogenes and L. innocua were determined in 6.3 % and 8.8 % of the samples respectively. At the end of initial 48 hours and 7 days enrichment Listeria species were present in total of 16.3 and 13.8 % sausage samples respectively. After 48 hours and 7 days enrichments of the same samples that were previously kept at -8 ± 1 °C for 10 days L. monocytogenes were present in 5.0 and 2.5 % whilst L. innocua occurred in 10.0 and 6.3 % of the samples respectively. In this examination overall positivity for Listeria species in sausage samples were 13.8 and 8.8 % at 48 hours and 7 days enrichments respectively. In chopped-meat samples after 48 hours enrichment L. monocytogenes and L. innocua were noticed in 11.4 and 18.6 % of79 samples. The results of 7 days enrichment showed the presence of L. monocytogenes and L. innocua in 8.6 and 1 1.4 % of the samples. In this examination overall positivity for Listeria species in chopped-maet samples were 28.6 and 20.0 % at 48 hours and 7 days enrichments respectively. After 48 hours and 7 days enrichements of the same samples that were previously kept at -8 ± 1 °C for 10 days L. monocytogenes were present in 7.1 and 5.7 % whilst L. innocua occurred in 12.9 and 10.0 % of the samples respectively. In this examination overall positivity for Listeria species in chopped-meat samples were 18.6 % at 48 enrichement and 15.7 % at 7 days enrichement respectively. In conclusion, Listeria Selective Agar (LSA) media seems superior to Modified McBride Agar (MMBA) and McBride Agar (MBA) media for isolation of Listeria species from meat samples. The results obtained from MMBA and MBA were similar. The rate of Listeria species contamination determined after 48 hours enrichment was higher than that obtained from 7 days enrichment. Most of the Listeria species were still viable after the samples being kept at -8 ± 1 °C for 10 days. L. monocytogenes contamination was higher particularly in minced meat and poultry meat samples, that should be concidered as a serious threat to public health.
Bu tezin, veri tabanı üzerinden yayınlanma izni bulunmamaktadır. Yayınlanma izni olmayan tezlerin basılı kopyalarına Üniversite kütüphaneniz aracılığıyla (TÜBESS üzerinden) erişebilirsiniz.
Keywords: Besin Hijyeni ve Teknolojisi; Food Hygiene and Technology